1998
DOI: 10.1073/pnas.95.11.6474
|View full text |Cite
|
Sign up to set email alerts
|

The effect of recombinant recoverin on the photoresponse of truncated rod photoreceptors

Abstract: Recoverin is a heterogeneously acylated calcium-binding protein thought to regulate visual transduction. Its effect on the photoresponse was investigated by dialyzing the recombinant protein into truncated salamander rod outer segments. At high Ca 2؉ (Ca), myristoylated recoverin (Carecoverin) prolonged the recovery phase of the bright f lash response but had less effect on the dim f lash response. The prolongation of recovery had an apparent K d for Ca of 13 M and a Hill coefficient of 2. The prolongation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…A main argument against such a role under in vivo conditions is the experimentally observed high IC 50 for [Ca 2ϩ ] free , which is about 1 order of magnitude higher than the cytoplasmic [Ca 2ϩ ] free in a darkadapted rod cell (41). However, it has been argued that the IC 50 value can be shifted into the physiologically relevant range when the data on rhodopsin kinase inhibition are extrapolated to the membrane-rich in vivo conditions of the rod cell (13,42 6%). These values are in the physiological range of free Ca 2ϩ in rod cells.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A main argument against such a role under in vivo conditions is the experimentally observed high IC 50 for [Ca 2ϩ ] free , which is about 1 order of magnitude higher than the cytoplasmic [Ca 2ϩ ] free in a darkadapted rod cell (41). However, it has been argued that the IC 50 value can be shifted into the physiologically relevant range when the data on rhodopsin kinase inhibition are extrapolated to the membrane-rich in vivo conditions of the rod cell (13,42 6%). These values are in the physiological range of free Ca 2ϩ in rod cells.…”
Section: Discussionmentioning
confidence: 84%
“…In cholesterol-containing DRMs, inhibition of rhodopsin kinase became more efficient at lower [Ca 2ϩ ] free . There has been a dispute in the literature (13,(41)(42)(43) about the physiological role of rhodopsin kinase inhibition by recoverin, but recent work on recoverin knockout mice has shown that the physiological role of recoverin is consistent with an effective prolongation of the catalytic activity of photoexcited rhodopsin (i.e. inhibition of rhodopsin kinase; Ref.…”
Section: Discussionmentioning
confidence: 99%
“…The best studied calcium myristoyl switch protein is recoverin, a calcium-binding protein in retinal rod cells that inhibits rhodopsin kinase only at high Ca 2ϩ levels (10,11) and regulates the recovery phase of phototransduction (12,13). In the resting dark state, recoverin binds two calcium ions and associates with retinal rod outer segment membranes through its exposed myristoyl group (6,7).…”
mentioning
confidence: 99%
“…We now have detailed information about the molecules that mediate this effect. As was first shown by Satoru Kawamura, rods contain a Ca¥-binding protein called S-modulin, also known as recoverin, that regulates the activity of Rh kinase (Kawamura & Murakami, 1991;Kawamura, 1993;Erickson et al 1998). It should also be noted that the effect of Ca¥ on the deactivation of rhodopsin is not its only action in the outer segment (Koutalos & Yau, 1996).…”
Section: Phototransductionmentioning
confidence: 98%